(untitled) (Bodhi Path, 2024)
The Shramana faith in India includes Jainism and Buddhism. A Shramana, also called Sramana in Sanskrit and Samana in Pali, is an itinerant monk in ascetic Indian traditions. Notable religious leaders among the Shramanas were Mahavira and Gautama Buddha. Vardhamana Mahavira was the founder of Jainism and the last Tirthankara of the Jainas. Among his many titles are "a great Brahmin," "a great preacher," "a great guardian," "a great pilot," and "a great recluse." He is also referred to as a Supreme Personality. He was born in 599 B.C. and died in 527 B.C. He was the second son of the Kshatriya family in Magadha1. His father, Siddhartha, belonged to the Kashyap gotra and the clan of Jnatrikas Kshatriyas, and his mother was Trisala. On the day of his birth, all prisoners were released, and public celebrations lasting ten days marked the occasion. At the age of 30, he left his family and set out in search of true knowledge On the other hand, Gautam Buddha was the founder of Buddhism. Born in Lumbini, near Kapilavastu, as a prince of the Kapilavastu monarch in 567 B.C., he abandoned his family to pursue enlightenment. He attained the higher knowledge at Gaya. During that period when both schools of thought were growing and expanding, there didn’t seem to be any competition between them. This is because both religions almost believed in the same facts and philosophy of life. However, they disagreed on certain views, such as salvation and the soul, which led them to part ways.